Mortality after breast cancer as a function of time since diagnosis by estrogen receptor status and age at diagnosis. Issue 12 (5th March 2019) - Jayasekara, Harindra; MacInnis, Robert J.; Chamberlain, James A.; Dite, Gillian S.; Leoce, Nicole M.; Dowty, James G.; Bickerstaffe, Adrian; Win, Aung Ko; Milne, Roger L.; Giles, Graham G.; Terry, Mary Beth; Eccles, Diana M.; et al.
Abstract : Our aim was to estimate how long‐term mortality following breast cancer diagnosis depends on age at diagnosis, tumor estrogen receptor (ER) status, and the time already survived. We used the population‐based Australian Breast Cancer Family Study which followed‐up 1, 196 women enrolled during 1992–1999 when aged <60 years at diagnosis with a first primary invasive breast cancer, over‐sampled for younger ages at diagnosis, for whom tumor pathology features and ER status were measured. There were 375 deaths (median follow‐up = 15.7; range = 0.8–21.4, years). We estimated the mortality hazard as a function of time since diagnosis using a flexible parametric survival analysis with ER status a time‐dependent covariate. For women with ER‐negative tumors compared with those with ER‐positive tumors, 5‐year mortality was initially higher ( p < 0.001), similar if they survived to 5 years ( p = 0.4), and lower if they survived to 10 years ( p = 0.02). The estimated mortality hazard for ER‐negative disease peaked at 3 years post‐diagnosis, thereafter declined with time, and at 7 years post‐diagnosis became lower than that for ER‐positive disease. This pattern was more pronounced for women diagnosed at younger ages. Mortality was also associated with lymph node count (hazard ratio (HR) per 10 nodes = 2.52 [95% CI:2.11–3.01]) and tumor grade (HR per grade = 1.62 [95% CI:1.34–1.96]). The risk of death following a breast cancer diagnosis differs substantially and qualitatively with diagnosis age, ER status and time survived. For women who survive >7 years, those with ER‐negative disease will on average live longer, and more so if younger at diagnosis. Abstract : What's new? To assess how estrogen receptor (ER) status and age at diagnosis are related to long‐term survival following diagnosis of breast cancer, authors conducted a large population‐based study, which was over‐sampled for young age at diagnosis, with a median follow‐up of 15 years. They found that for women who survived >7 years, those with ER‐negative disease were predicted to live longer, especially if diagnosed at a younger age.